1989
DOI: 10.1164/ajrccm/139.2.407
|View full text |Cite
|
Sign up to set email alerts
|

Ozone-induced Inflammation in the Lower Airways of Human Subjects

Abstract: Although ozone (O3) has been shown to induce inflammation in the lungs of animals, very little is known about its inflammatory effects on humans. In this study, 11 healthy nonsmoking men, 18 to 35 yr of age (mean, 25.4 +/- 3.5), were exposed once to 0.4 ppm O3 and once to filtered air for 2 h with intermittent exercise. Eighteen hours later, bronchoalveolar lavage (BAL) was performed and the cells and fluid were analyzed for various indicators of inflammation. There was an 8.2-fold increase in the percentage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
214
2
4

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 473 publications
(230 citation statements)
references
References 9 publications
10
214
2
4
Order By: Relevance
“…Acute ozone inhalation in humans has been shown to result in the elevation in BAL fluid of several macromolecules normally restricted to the vascular compartment that may contribute to cellular injury and necrosis, including complement 3a (39). Interestingly, Park and colleagues (40) have recently demonstrated that either depleting and/or antagonizing complement in mice significantly reduces ozoneinduced airway hyperresponsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Acute ozone inhalation in humans has been shown to result in the elevation in BAL fluid of several macromolecules normally restricted to the vascular compartment that may contribute to cellular injury and necrosis, including complement 3a (39). Interestingly, Park and colleagues (40) have recently demonstrated that either depleting and/or antagonizing complement in mice significantly reduces ozoneinduced airway hyperresponsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…A complex sequence of events is involved in the inflammatory process, each step of which can have detrimental effects on the lung and its host defense functions (62 (64). Mineral dust particles such as quartz, asbestos, and silica induce pulmonary inflammation and activate immune cells to produce ROS.…”
Section: Airway Inflammationmentioning
confidence: 99%
“…In addition, increased exposure to O3 has been linked to increased incidences of diabetes mellitus type I [18] . Moreover, inflammation induced by exposure to O3 in humans has been reported [19] . Although most of the damage by O3 occurs in the lungs due to inhalation, it has been shown to cause oxidation or peroxidation of biomolecules such as DNA, proteins, lipids, leading to a vicious cycle of chronic inflammation and oxidative stress commonly seen in diabetes [13] .…”
Section: Climate Change and Diabetes Mellitusmentioning
confidence: 99%